Dealing with sleep problems during home confinement due to the COVID‐19 outbreak: Practical recommendations from a task force of the European CBT‐I Academy. (4th May 2020) - Altena, Ellemarije; Baglioni, Chiara; Espie, Colin A.; Ellis, Jason; Gavriloff, Dimitri; Holzinger, Brigitte; Schlarb, Angelika; Frase, Lukas; Jernelöv, Susanna; Riemann, Dieter
ABSTRACT: In the current global home confinement situation due to the COVID‐19 outbreak, most individuals are exposed to an unprecedented stressful situation of unknown duration. This may not only increase daytime stress, anxiety and depression levels, but also disrupt sleep. Importantly, because of the fundamental role that sleep plays in emotion regulation, sleep disturbance can have direct consequences upon next day emotional functioning. In this paper, we summarize what is known about the stress−sleep link and confinement as well as effective insomnia treatment. We discuss those effects of the current home confinement situation that can disrupt sleep but also those that could benefit sleep quality. We suggest adaptions of cognitive behavioural therapy elements that are feasible to implement for those facing changed work schedules and requirements, those with health anxiety and those handling childcare and home‐schooling, whilst also recognizing the general limitations imposed on physical exercise and social interaction. Managing sleep problems as best as possible during home confinement can limit stress and possibly prevent disruptions of social relationships.